Mice and Rats Display Different Ventilatory, Hematological, and Metabolic Features of Acclimatization to Hypoxia - Arias-Reyes, Christian; Soliz, Jorge; Joseph, Vincent (Frontiers in Physiology, 2021)
Phylogeographic studies showed that house mice (Mus musculus) originated in the Himalayan region, while common rats (Rattus rattus and Rattus norvegicus) come from the lowlands of China and India. Accordingly, it has been proposed that its origins gave mice, but not rats, the ability to invade ecological niches at high altitudes (pre-adaptation). This proposal is strongly supported by the fact that house mice are distributed throughout the world, while common rats are practically absent above 2,500 m. Considering that the ability of mammals to colonize high-altitude environments (> 2,500 m) is limited by their capability to tolerate reduced oxygen availability, in this work we hypothesize that divergences in the ventilatory, hematological, and metabolic phenotypes of mice and rats establish during the process of acclimatization to hypoxia. To test this hypothesis male FVB mice and SD rats were exposed to hypoxia (12% O2) for 0 hours (normoxic controls), 6 hours, 1, 7, and 21 days. We assessed changes in ventilatory (minute ventilation [VE], respiratory frequency [fR], and tidal volume [VT]), hematological (hematocrit and hemoglobin concentration), and metabolic (whole-body O2 consumption [VO2] and CO2 production [VCO2], and liver mitochondrial oxygen consumption rate [OCR]) parameters). Compared to rats, results in mice show increased ventilatory, metabolic and mitochondrial response. In contrast, rats showed quicker and higher hematological response than mice and only minor ventilatory and metabolic adjustments. Our findings may explain, at least in part, why mice, but not rats, were able to colonize high-altitude habitats.